Reflections from the COVID‐19 pandemic on inequalities and patient and public involvement and engagement (PPIE) in social care, health and public health research. (9th August 2021) - Clark, Michael; van Vliet, Esther; Collins, Michelle
Abstract: Patient and public involvement and engagement (PPIE) has evolved to become widely established practice in social care, health and public health research in the UK. The COVID‐19 pandemic has caused rapid change in practice in PPIE, notably in moving from face‐to‐face meetings to virtual ones. This has opened a space for reflecting on established PPIE practice, but there is a risk this is conducted too narrowly, such as only weighing our preferences and the relative pros and cons with regard to in‐person versus virtual meetings. The pandemic has also demonstrated the wide inequalities in society, and hence, we argue that an inequalities lens ought to guide a deeper and wider reflection on PPIE practice. We do not seek to criticize practice pre‐ or during the pandemic, but to encourage using the inequalities lens as a means of encouraging debate and focusing energy on a more rigorous review of PPIE practice to widen involvement in social care, health and public health research.